2015
DOI: 10.1016/j.exger.2015.06.019
|View full text |Cite
|
Sign up to set email alerts
|

Feeding on frozen live yeast has some deleterious effects in Drosophila melanogaster

Abstract: Colinet. Feeding on frozen live yeast has some deleterious effects in Drosophila melanogaster. Experimental Gerontology, Elsevier, 2015, 69, pp.202-210. 10 severe stresses and behaviour in Drosophila melanogaster flies. The present study tested whether feeding flies with frozen yeast rather than with fresh yeast could have some effect on these traits, the other components of the food being similar in the two groups. Freezing altered live yeast quality and flies feeding on frozen yeast lived slightly less (mal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 37 publications
2
5
0
Order By: Relevance
“…Our restriction was more severe than that of Burger et al (2007) who used a restrictive diet comparable to our intermediate diet (8:8), which could explain this result. The lower knockdown temperature in yeast-rich and sugar-poor diet 2:16 diet is consistent with previous observations that excess in dietary sugar is not necessarily beneficial for cold tolerance (Colinet et al, 2013) and that yeasts, especially live ones, favor cold tolerance (Colinet and Renault, 2014;Le Bourg et al, 2015). Although increased cold tolerance of microbiota-altered flies is surprising , it could be linked to the unexpected increased yeast gut content that resulted from our antibiotic treatment.…”
Section: Consequences Of Diet-microbiota Interactions On Stress Tolersupporting
confidence: 90%
See 1 more Smart Citation
“…Our restriction was more severe than that of Burger et al (2007) who used a restrictive diet comparable to our intermediate diet (8:8), which could explain this result. The lower knockdown temperature in yeast-rich and sugar-poor diet 2:16 diet is consistent with previous observations that excess in dietary sugar is not necessarily beneficial for cold tolerance (Colinet et al, 2013) and that yeasts, especially live ones, favor cold tolerance (Colinet and Renault, 2014;Le Bourg et al, 2015). Although increased cold tolerance of microbiota-altered flies is surprising , it could be linked to the unexpected increased yeast gut content that resulted from our antibiotic treatment.…”
Section: Consequences Of Diet-microbiota Interactions On Stress Tolersupporting
confidence: 90%
“…The focus is often on bacteria as the main gut symbionts but the role of yeasts should not be neglected (Hoang et al, 2015). Live yeasts can affect Drosophila physiology and increase survival to infections and starvation, in addition to cold stress (Le Bourg et al, 2015;Le Rohellec and Le Bourg, 2009). The difference between the effects of dead and live yeasts suggests these microorganisms provide an active protection that goes beyond being a simple food source.…”
Section: Consequences Of Diet-microbiota Interactions On Stress Tolermentioning
confidence: 99%
“…melanogaster studies have shown that the quality of the fungal diet, provided either throughout life or only at the adult age, can affect adult life traits. For example, adults fed with frozen or heat-killed yeast showed altered development, lower fertility, shorter life span and increased sensitivity to stress than did adults fed on a fresh yeast diet 11 . Furthermore these effects persisted even when a 600-fold increased amount of heat-killed yeast was added to the diet 12 .…”
Section: Introductionmentioning
confidence: 99%
“…1 in Le Bourg, 2021a) were however not used to observe lifespan. Flies used in the present article were the control groups of several articles observing the effect of various factors on lifespan (Le Bourg, 2007Bourg, , 2010Bourg, , 2011Bourg, , 2012Bourg, , 2021bLe Bourg and Lints, 1989;Le Bourg and Medioni, 1991;Le Bourg et al, 2000, 2002, 2015Le Rohellec and Le Bourg, 2009), and were subjected to the very same rearing conditions (see below). The mean viability in the present study was 74.42% (26 groups, range: 41.37-87.09%).…”
Section: Methodsmentioning
confidence: 99%